Transcriptomic analysis reveals that selenium-enriched Lactobacillus plantarum alleviates high -salinity stress in common carp through lipid metabolism and ferroptosis signalling pathways - Xinchi Shang; Xinghua Che; Longwu Geng; Qing Zhang; Haijun Wei; Wang Li; Xiaodan Shi; Wei Xu (Ecotoxicology and Environmental Safety, 2025)
Inland water resource salinisation is a global problem. High salinity leads to increased pressure on the survival of aquatic animals, severely limiting the development of the aquaculture industry. Salinity stress disrupts antioxidant defences in aquatic animals and results in oxidative stress, damaging body functions. As an important constituent of glutathione, selenium has been shown to play an important role in improving antioxidant defences and regulating metabolism. Biological methods for synthesising selenium nanoparticles (Bio-SeNPs) using Lactobacillus plantarum are safe, inexpensive, and readily available. However, how selenium-enriched Lactobacillus plantarum (SL) alleviates salinity stress-mediated oxidative damage and metabolic disorders and the underlying molecular mechanisms remain to be elucidated. In this study, 270 common carp were randomly divided into a control group (salinity: 0.02 ppt), a high salinity group (HS group, salinity: 12 ppt), and a high salinity plus SL group (FXHS group, salinity: 12 ppt) and cultured for 8 weeks. The analyses included histopathology, detection kits, transcriptomics, and quantitative real-time PCR. Histopathology revealed that salinity stress resulted in vacuolisation of hepatocytes, nucleolysis, incomplete nucleoli, and nonagglutinating chromatin in the cell nucleus of the liver; decreased mitochondria; increased mitochondrial membrane density; reduced or absent mitochondrial cristae; and an increased outer mitochondrial membrane. After the addition of SL, the hepatocytes exhibited normal chromatin, intact nucleoli, reduced mitochondrial cristae damage, and intact mitochondrial membranes. High-salinity stress leads to lipid metabolism disruption and reduced activity of antioxidant and immune-related enzymes, ultimately leading to oxidative stress and lipid peroxidation. After SL addition, the salinity-mediated oxidative stress and lipid metabolism abnormalities were significantly reversed. Transcriptomics method revealed 3975 differentially expressed mRNAs (DEGs) in the liver (HS vs. C), with 2251 upregulated genes and 1724 downregulated genes. There were 1861 differentially expressed genes (DEGs) (FXHS vs. C) in the liver, 1312 genes with upregulated expression, and 549 genes with downregulated expression. KEGG enrichment analysis revealed that the FOXO, PPAR, glutathione metabolism, and ferroptosis signalling pathways were involved in high-salinity stress-related molecular mechanisms. Salinity stress downregulates ACSL1 and acyl-CoA desaturase, inhibiting the expression of PPARs and the ligand RXRs, leading to blocked fatty acid oxidation; increases fatty acid synthesis by promoting acetyl coenzyme A carboxylase, leading to lipid accumulation; promotes the expression of ACSL4, NOX2, ZIP14 and LPCAT3, triggering ferroptosis; and inhibits the expression of fth1, gsto1 and the Xc-/GSH/GPX4 axis, reducing resistance to ferroptosis. SL may alleviate high-salinity stress-mediated oxidative stress, lipid metabolism disorders, and ferroptosis through the PPAR and ferroptosis signalling pathways. Our study revealed that SL may alleviate oxidative stress and ferroptosis.